Parking state in the inner central area of Belgrade - Simićević Jelena R.; Čuljković Vladimir V.; Nikolić Tijana A. (Tehnika, 2025)
In accordance with the modern approach to parking management, a restrictive parking regime in the central area of Belgrade was introduced in 2003. Since then, the area where the regime is applied has been increased several times. The regime attributes, parking supply and the enforcement system have also changed. In addition, the number of registered passenger cars in Belgrade has doubled. Although the permanent monitoring of the state is a prerequisite for successful management, to the best of our knowledge, parking state in the central area has not been adequately evaluated for many years, despite all above mentioned changes. This was the motive for writing this article, which aims to examine and evaluate parking state in the inner central area of Belgrade. Analysing the data obtained by field surveys and taken from the Parking Servis site, it was assessed that the state is not good. This article further identifies the causes of the problem and proposes possible directions for state improvement.